Functional food consumption and its associated factors among university students in Malaysia during COVID-19 Pandemic - Ee, Janice Fang Tay; En, Serene Hui Tung; Kai, Ting Mok; Choon, Hui Tan; Wan, Ying Gan; Wai, Chuen Poon (Universiti Sains Malaysia, 2023)
Background: In the current situation of COVID-19, dietary intake that incorporates functional foods may potentially be a preventive measure for defence against viral infection. This study aimed to determine the consumption of functional foods and its associated factors among university students during COVID-19. Methods: This was a cross-sectional study conducted among 284 Malaysian university students in Kuala Lumpur, Malaysia. An online self-administered questionnaire was employed to assess subjects nutrition knowledge, dietary habits, attitude towards functional foods, recognition and consumption of functional food products. Results: Out of 284 respondents, 41.9 had poor level of nutrition knowledge and 57 had moderate level of functional food-related attitude, with seven types of functional foods consumed on average (57.0). Binary logistic regression showed that university students who consumed fruits at least three times per day (aOR = 11.18; 95 CI: 1.46, 80.17), salty snacks (aOR = 2.90; 95 CI: 1.43, 5.86), soft drinks/sugar-sweetened beverages (SSB) (aOR = 3.12; 95 CI: 1.53, 5.26) and pure juice (aOR = 2.80; 95 CI: 1.48, 5.30) were more likely to consume functional foods during COVID-19 (P < 0.05). Conclusion: The findings could provide information to public and private sectors in terms of creating a supportive environment to encourage and promote the awareness and consumption of functional foods and their associated health benefits.